2018
DOI: 10.1051/matecconf/201817701017
|View full text |Cite
|
Sign up to set email alerts
|

Sea level rise impact modelling on small islands: case study gili raja island of east java

Abstract: Abstract. Coastal regions and small islands are areas that will be adversely affected by the phenomenon of sea level rise globally. In general, Sea Level Rise (SLR) will result in coastal impacts as follows: increased frequency and intensity of floods, changes in ocean currents and widespread intrusion of sea water. This research was conducted in Gili Raja Island of Sumenep Madura. Objectives of this research were to demonstrate the ability of combining remote sensing and GIS method to determine the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(10 reference statements)
0
4
0
1
Order By: Relevance
“…Berdasarkan data dari Intergovernmental Panel on Climate Change (IPCC) tahun 2013, rata-rata kenaikan suhu permukaan laut di bumi adalah 0,3-0,6 °C sejak akhir abad ke 19. Apabila menggunakan kecenderungan tersebut, maka pada tahun 2100 suhu permukaan laut di bumi diperkirakan naik hingga 1,4 °C (Andre, 2013;Hidayah et al, 2018). Akibat dari kenaikan suhu permukaan laut tersebut, maka laju pencairan es di kutub utara dan selatan akan semakin cepat dan pada akhirnya akan menyebabkan kenaikan permukaan air laut.…”
Section: Pengantarunclassified
“…Berdasarkan data dari Intergovernmental Panel on Climate Change (IPCC) tahun 2013, rata-rata kenaikan suhu permukaan laut di bumi adalah 0,3-0,6 °C sejak akhir abad ke 19. Apabila menggunakan kecenderungan tersebut, maka pada tahun 2100 suhu permukaan laut di bumi diperkirakan naik hingga 1,4 °C (Andre, 2013;Hidayah et al, 2018). Akibat dari kenaikan suhu permukaan laut tersebut, maka laju pencairan es di kutub utara dan selatan akan semakin cepat dan pada akhirnya akan menyebabkan kenaikan permukaan air laut.…”
Section: Pengantarunclassified
“…Such management is essential because most industries are located in coastal areas. As a result, the areas experience reasonably fast economic growth (Hidayah et al, 2018). In coastal management, the need for water depth information (bathymetry) is critical (Prayogo & Basith, 2020) because the data can be used for various purposes in hydrography, such as coastal engineering and shipping trajectory (Gao, 2009;Jupp, 1989;Leu & Chang, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This is integrally linked to the fact that Indonesia has thousands of small islands scattered across the country. Previous studies have explored the condition of Bawean Island particularly its coastal and marine environment, including biological diversity (Asaad et al, 2018), small island ecosystems including mangroves (Muhtadi et al, 2020), seagrass (Brodie et al, 2020), coral reefs (Hafezi et al, 2020) and vulnerability to sea-level rise as the results of global climate change (Hidayah et al, 2018;Stephenson & Jones, 2017;Jamero et al, 2017). While many studies focussed on the state of the coastal environment and ecosystems of Bawean Island, there was no studies have been reported regarding the island's land cover dynamic.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies on Bawean Island have been conducted in the last five years, but the majority of them have focused on the condition of the coastal environment, conservation, and suitability for ecotourism activities (Hidayah et al, 2018;Sukandar et al, 2017;Wardani et al, 2017b). Because of the abundance of coral reefs surrounding the island, more detailed studies have been conducted to determine the state of the ecosystem (Dharmawan et al, 2020;Luthfi & Anugrah, 2017).…”
Section: Introductionmentioning
confidence: 99%